AN INDEX OF DEPRESSION IN PATIENTS WITH CHRONIC NONSPECIFIC MUSCULOSKELETAL PAIN - Afzal, Naeema; Ali, Nasir; Shakoor, Abdus; Mahmud, Tafazzul -e-Haque; Jahan, S Shah (Journal of Ayub Medical College Abbottabad, 2005)
Background: The present study was undertaken to derive an index of depression in patients with chronic non-specific musculoskeletal pain and to determine correlation between these two parameters. Method: The study was carried out at the Shaikh Zayed Hospital Lahore from November 2001 to May 2002 and included 36 patients with pain for at least 4-24 weeks duration; an equal number of healthy people acted as controls. Depression was assessed among subjects by administering the General Health Questionnaire (GHQ) to patients and controls and obtaining their GHQ scores. Pain assessment was performed in patients by scoring the total number of pain sites on digital palpation to provide a Total Pain Score (TPS). Results: Patients differed significantly from controls in their GHQ scores (patients 20.47 ± 7.19, controls 3.11 ± 1.89 respectively, p<0.001). The GHQ score and the TPS score correlated significantly in patients (r=0.517, p=0.001). Conclusions: Patients with chronic non-specific musculoskeletal pain suffer from significant levels of depression, in direct correlation to their pain. Key Words: Depression, Chronic pain, Musculoskeletal pain